Comentarios sobre el entorno empresarial: la variable política - Silva Vegas, Gerardo (1992)
It aims to provide the manager, in his capacity as the leader of an organization that produces goods or services for society, an analytical instrument that allows him to decompose the most complex external factor: the political variable, understood as power relations, the interaction of social groups with different or antagonistic interests, and decision-making by socially powerful subjects that affects the whole. To approach the compression of this variable, an analytical instrument is proposed which combines four dimensions: contradiction between capital and labor, contradiction between State and civil society, contradiction between violence and peace and national contradiction (between protectionism and globalization or between nationalism and internationalism). Other dimensions are conceivable; however, what is important is the usefulness of the analytical method for the stated purposes. The analysis of the political variable will allow the company’s adequate understanding and, consequently, the possibility of predicting its behavior and anticipating the events.